Zinc deficiency as a key risk factor for pneumonia in early childhood: a hospital-based case-control study - Jacob, Linda; Cherian, Carol Sara (International Journal of Research in Medical Sciences, 2026)
Background: Pneumonia remains the leading infectious cause of under-five mortality globally. Zinc deficiency impairs immune function and is prevalent among children in low- and middle-income countries. This study examined the association between serum zinc status and pneumonia in hospitalised children aged 6-59 months at a tertiary care centre in Kerala, India. Methods: A prospective hospital-based case-control study was conducted from May 2023 to November 2024. Thirty children with WHO-defined pneumonia (cases) were compared with 30 age- and sex-matched healthy controls. Serum zinc was measured by atomic absorption spectrometry. Zinc deficiency was defined per IZiNCG criteria as <65 µg/dl. Logistic regression estimated the odds of pneumonia per 1 µg/dl decrease in serum zinc. Results: Mean serum zinc was significantly lower in cases than controls (54.0±11.6 µg/dl versus 76.8±13.6 µg/dl; mean difference 22.8 µg/dl, 95% CI 16.2-29.3; p<0.001). Zinc deficiency was present in 86.7% of cases (33.3% severe, 53.3% mild) versus 26.7% of controls (p<0.001). Each 1 µg/dl decrease in serum zinc was associated with 1.15-fold greater odds of pneumonia (OR 1.15, 95% CI 1.07-1.24; p<0.001). No significant associations were found with anthropometric indices, disease severity, or length of hospital stay. Conclusions: Low serum zinc was strongly associated with childhood pneumonia, even among children with normal growth parameters, consistent with the ‘hidden hunger’ phenomenon. Prospective multi-centre studies are needed to confirm these findings.